In vitro and in silico evaluation of phytocompounds from Leucaena leucocephala and Entada phaseoloides targeting DNA gyrase, topoisomerase II, AKT1 - Laldinliana Khiangte; Hmingremhlua Sailo; Laldinfeli Ralte; F. Lalnunmawia; N. Senthilkumar; Yengkhom Tunginba Singh (Scientific Reports)
Abstract Medicinal plants are rich in bioactive phytochemicals with the potential to treat various ailments, including cancer and infectious diseases. Leucaena leucocephala and Entada phaseoloides have long been used in traditional medicine for such conditions. This study investigated the phytochemical composition, antioxidant, antibacterial, and anticancer potential of methanolic pod extracts of both species through integrated in vitro and in silico approaches. L. leucocephala exhibited higher total phenolic content (49.02 ± 0.43 GAE/g) and total flavonoid content (77.95 ± 0.32 QE/g) than E. phaseoloides (TPC: 42.30 ± 0.13 GAE/g; TFC: 72.90 ± 0.42 QE/g). Phytochemicals were characterized via FTIR and LC–MS, identifying 54 compounds. Antioxidant activity assessed by DPPH and ABTS assays showed stronger radical scavenging in L. leucocephala (IC50: 51.53 ± 0.40 and 38.68 ± 0.20 µg/mL) than in E. phaseoloides (IC50: 73.29 ± 0.48 and 64.63 ± 0.29 µg/mL). Cytotoxicity assays against HeLa cells demonstrated potent anticancer activity, with IC50 values of 3.83 ± 0.07 µg/mL for L. leucocephala and 4.71 ± 0.06 µg/mL for E. phaseoloides. In silico ADMET profiling, molecular docking, and molecular dynamics simulations identified key bioactive compounds with strong binding affinities toward Topoisomerase II, DNA gyrase, and AKT1. Protein–ligand complexes showed high stability through consistent RMSD, low RMSF, strong hydrogen bonding, and stable SASA values, supporting their therapeutic relevance. This is the first comprehensive pharmacological study on pod extracts of L. leucocephala and E. phaseoloides from Mizoram, India. The findings provide compelling evidence for their development as promising candidates for antibacterial and anticancer drug discovery.